FACEBOOK AS A MEDIATION OF PEER ASSESSMENT: EXPLORING CHALLENGES AND BENEFITS IN AN EFL SPEAKING CLASSROOM SETTING - Nita Puspitasari; Metty Agustine Primary (Siliwangi University, 2018)
The purpose of this study was to address students’ perceptions about integrating Facebook as the mediation of peer assessment in EFL Speaking Classroom. The participants of this study consist of four students in the fourth semester pursuing English Education major in an Indonesian university. The data was collected by semi-structured interview and then the data were analyzed qualitatively, and interpretively by using thematic analysis. The result indicates four emerging themes about the students’ perception on using FB as the mediation of peer assessment; challenges encountered by the students during FB-mediated peer assessment, the importance of being an autonomous learner, FB as a platform to build speaking learning motivation, and FB as a platform to build speaking learning confidence. This study provided language instructors with insights into the adoption of Facebook in an EFL context and supported them with better design tasks on FB.